Painting Without Paint: Four Sisters, Three Dresses. (11th November 2022) - Barwari, Nuveen
Abstract : Nuveen Barwari uses the multiple layers of the jilli Kurdi (Kurdish dress) as a metaphor for the multiple layers of a Kurdish diasporic identity. Using Édouard Glissant's concept of opacity, Barwari engages with the jilli Kurdi as artistic inspiration, describing it as private space for an individual, and for a diasporic community as anapparatus that works in opposition to transparency, protecting the unseen, and resisting a colonial gaze.